Na-modified ferrocobalt solid solution catalyst, preparation thereof and application of catalyst in reaction for preparing high-carbon alcohol and co-producing high-carbon olefin from synthesis gas

Preparation of Na-CoFeOX catalyst by concurrent titration solves the problems of low CO conversion and insufficient selectivity of existing catalysts, achieving efficient CO conversion and high-carbon alcohol olefin selectivity, and significantly improving the catalyst stability.

CN119500144AActive Publication Date: 2025-02-25DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411598161.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-25
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing synthesis gas conversion catalysts have problems such as low CO conversion, low selectivity of high carbon alcohol and olefins, and unstable catalysts, resulting in insufficient reaction efficiency and product selectivity.

Method used

The preparation strategy of co-flow titration is adopted to prepare a Na-CoFeOX solid solution catalyst by co-flowing with nitrate by a special precipitant and nitrate. The oxygen vacancy in the catalyst is used to improve the adsorption and insertion capacity of CO, and the hydrogenation reaction is inhibited by carbonization of metal cobalt and iron to enhance the stability of the catalyst.

Benefits of technology

The conversion rate of CO and the selectivity of high carbon alcohols and olefins are significantly improved, and the service life of the catalyst is extended. The catalyst has no obvious inactivation in the 1000-hour reaction, and has high activity and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005127506850000061
    Figure BDA0005127506850000061
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-efficiency Na-modified solid solution catalyst and application of the Na-modified solid solution catalyst in a reaction for preparing high-carbon alcohol and co-producing high-carbon olefin from synthesis gas. The catalyst comprises a solid solution component and an auxiliary agent component, the solid solution component is a ferrocobalt solid solution, the auxiliary agent component is a sodium elementary substance or oxide, and a reaction active center is the ferrocobalt solid solution, cobalt and cobalt carbide or cobalt oxide species and the sodium elementary substance or oxide. The invention provides a preparation method and application of a novel Na modified ferrocobalt solid solution catalyst, the catalyst has high activity, high C6 + alcohol and C5 + olefin selectivity and stability, the operation temperature can be in a range of 200-350 DEG C, and the reaction pressure is in a range of 0.5-10 MPa. The catalyst is stable in structure in the reaction process, the preparation method is simple and easy to repeat, and industrial application is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing an efficient Na-modified solid solution catalyst and its application in syngas conversion, which is applied to catalyzing syngas to prepare high-carbon alcohols and co-produce high-carbon olefins with high selectivity. In particular, it relates to a Na-CoFeO X Preparation method and application of catalyst. Background Art

[0002] High-carbon alcohols usually refer to alcohols containing six or more carbon atoms. They are an important component of the chemical, pharmaceutical and energy fields and have great economic value. The traditional route for preparing high-carbon alcohols from petroleum is a complex chemical process, which mainly includes the cracking of petroleum into low-carbon olefins, then polymerization into long-chain olefins, hydroformylation of long-chain olefins into aldehydes, and further hydrogenation into alcohols. Compared with the traditional synthetic route, the one-step synthesis of high-carbon alcohols by syngas conversion is a more efficient, relatively simple and environmentally friendly process. Long-chain olefins usually refer to linear α-olefins with 5 or more carbon atoms. They are important organic raw materials and are used as comonomers for various types of polyethylene, as well as for the synthesis of high-quality lubricants and plasticizers. The main production method of long-chain α-olefins is the ethylene oligomerization reaction of the petroleum route. With the continuous consumption of petroleum resources, the preparation of olefins by non-petroleum routes has attracted much attention. This route mainly uses carbon-containing resources such as coal, natural gas, and biomass to prepare syngas, and further directly or indirectly produces olefins. However, this reaction process is very complicated. CO and H2 are difficult to be activated and cracked during the reaction, resulting in the problem of low catalyst reactivity. At the same time, a series of byproducts such as methane, carbon dioxide, and alkanes are produced during the reaction, resulting in low selectivity for high-carbon alcohols and olefins. Therefore, it is still challenging to regulate the reaction network through catalyst design to achieve the synergistic effect of different active sites, so as to preferentially form high-carbon alcohols and olefins through direct conversion of syngas.

[0003] Various types of high-carbon alcohol synthesis catalysts have been studied in the patents currently applied for. Patent CN102500374B reports a copper-based multi-metal nanocatalyst prepared by self-reduction, distributed reduction, and simultaneous reduction, which improves the C 2+ and C 6+ However, the CO conversion rate in the patent document is low, the selectivity and yield of total alcohol and olefins are low, and a large amount of CO2 by-products will be produced during the reaction. Patent CN102319575A discloses a method with high C 5+Cu-Fe catalyst with alcohol selectivity has low cost, simple preparation method and stable performance. However, the alcohol distribution obtained by the catalyst is concentrated in C1-C4 alcohol, and the selectivity of high-carbon alcohol is low. Patent CN 105664964 B reports a Cu and Co mixed oxide catalyst for preparing high-carbon alcohol from synthesis gas, which has the advantages of high activity and high total alcohol selectivity, but metallic copper is easily agglomerated and deactivated during the reaction, resulting in a short life of the catalyst. In summary, the synthesis gas preparation of high-carbon alcohol catalysts reported in the current patent generally have low synthesis gas conversion rate and low selectivity of high-carbon alcohol and olefin. The problem of unstable catalyst still needs further improvement. Summary of the invention

[0004] The purpose of the present invention is to prepare Na-CoFeO by using a preparation strategy of co-current titration of a special precipitant and nitrate. X Solid solution catalysts improve the adsorption and carbon chain insertion capabilities of CO through oxygen vacancies in the catalyst, thereby improving the CO conversion rate and the selectivity of high-carbon alcohols and olefins. The metal cobalt and iron are carbonized into carbides during the reaction process to inhibit the hydrogenation reaction and reduce the generation of CH4. At the same time, the strong interaction between the two metals makes the reaction active center easy to control and stabilize, thereby improving the stability of the catalyst. The catalyst did not show obvious deactivation after 1000 hours of reaction.

[0005] Na-CoFeO X Preparation process of solid solution catalyst:

[0006] (1) dissolving a soluble salt of Co and a soluble salt of Fe in 20-100 ml of ethanol at a metal molar ratio of 5:1-50:1 to prepare a mixture;

[0007] The soluble salt of Co is one or more of cobalt nitrate, cobalt acetate, cobalt sulfate and cobalt hydrochloride; the soluble salt of Fe is one or more of ferric nitrate, ferric acetate, ferric chloride and ferrous sulfate;

[0008] (2) preparing a 0.1 mol / L to 10 mol / L aqueous solution of a precipitant, wherein the precipitant is one or more of potassium hydroxide, ammonium chloride, ammonium carbonate, and sodium hydroxide.

[0009] (3) Add 0.5-3 g of soluble salt of Na to the mixture treated in step (1), mix ultrasonically at 35-50° C. for 6-10 hours, and then add the solutions of steps (1) and (2) in a co-current manner at 50-150° C. at a flow rate of 0.01 ml / min-0.5 ml / min using a peristaltic pump at a pH of 7-10.

[0010] The soluble salt of Na is one or more of sodium nitrate, sodium chloride, sodium carbonate and sodium sulfate.

[0011] (4) treating the mixture after the treatment in step (3) by rotary evaporation at 50-100° C. for 5-15 h, washing with deionized water and filtering to obtain a filter cake;

[0012] (5) The filter cake obtained in step (4) is vacuum dried at 50-100°C for 5-20h, and then dried at a gas space velocity of 2000-4000h -1 Calcine at 600-1100℃ for 5-15h in an argon atmosphere to obtain Na-CoFeO X Solid solution catalyst.

[0013] The Na-CoFeO X Solid solution catalysts can be used in the synthesis gas conversion reaction to prepare high carbon alcohols and co-produce high carbon olefins. The catalyst is first loaded into the constant temperature zone of the reaction tube, and the entire reaction tube is filled with quartz sand. Before use, the catalyst is reduced and activated in hydrogen or a hydrogen-inert gas mixture at a temperature of 300-600°C, a reduction activation time of 1-50h, and a gas space velocity of 200-10000h. -1 After activation, the reaction conditions are adjusted to the specified conditions, where the volume ratio of H2 to CO in the synthesis gas is 0.5-10, the reaction temperature is 180-350°C, the reaction pressure is 0.5-10MPa, and the synthesis gas space velocity is 500-8000h -1 .

[0014] The beneficial effects of the present invention are as follows: a new method for preparing a parallel flow titration solid solution catalyst is proposed, and Na-CoFeO X The catalyst is used in the reaction of preparing high-carbon alcohols and co-producing high-carbon olefins by converting synthesis gas. The oxygen vacancies in the catalyst improve the ability of CO adsorption and insertion into carbon chains, thereby improving the CO conversion rate and the selectivity of high-carbon alcohols and olefins. The metal cobalt and iron are carbonized into carbides during the reaction process to inhibit the hydrogenation reaction and reduce the generation of CH4. At the same time, the strong interaction between the two metals is used to make the reaction active center easy to control and stabilize. Thus, the stability of the catalyst is improved. The catalyst did not show obvious deactivation after 1000h of reaction.

[0015] The catalyst has high activity, high C 6+ Alcohol and C 5+ Olefin selectivity and stability, the operating temperature can be carried out in the range of 200-350℃, and the reaction pressure is between 0.5MPa-10MPa. The catalyst structure is stable during the reaction process, the preparation method is simple, easy to repeat, and conducive to industrial application. DETAILED DESCRIPTION

[0016] In order to better understand the present invention, the technical solution of the present invention is described in detail below in conjunction with embodiments. The embodiments do not limit the protection scope of the present invention.

[0017] Example 1

[0018] (1) Take 2 g of cobalt nitrate hexahydrate and 0.3 g of ferric acetate, dissolve them in 30 ml of ethanol and mix well.

[0019] (2) Take 1.5 g of ammonium chloride and 2 g of sodium hydroxide and dissolve them in deionized water to prepare a precipitant with a total concentration of 3 mol / L.

[0020] (3) Add 1 g of sodium nitrate to the mixture after treatment in step (1), and mix them ultrasonically at 50° C. for 6 hours to obtain a mixed solution. Then, the mixed solution and the solution of step (2) are added dropwise to the same container using a peristaltic pump in a co-current addition strategy, and are added dropwise at 100° C. at a flow rate of 0.1 ml / min until the pH reaches 8.

[0021] (4) The mixture treated in step (3) was subjected to rotary evaporation at 50° C. for 10 h, and then washed with deionized water and filtered to obtain a filter cake.

[0022] (5) The obtained filter cake was vacuum dried at 80°C for 12 h and finally dried under argon atmosphere at a space velocity of 3000 h -1 , calcined at 800℃ for 10h to obtain Na-CoFeO X catalyst.

[0023] The catalyst was first activated at 400 °C for 5 h under hydrogen conditions with a gas space velocity of 2000 h -1 Then, the volume ratio of H2 to CO was 3, the reaction temperature was 250℃, the reaction pressure was 5MPa, and the synthesis gas space velocity was 6000h -1 The reaction was carried out under the conditions of , and the results are shown in Table 1.

[0024] Example 2

[0025] (1) Take 3 g of cobalt acetate and 0.8 g of ferric acetate, dissolve them in 50 ml of ethanol and mix well.

[0026] (2) Take 2.3 g of ammonium chloride and 3 g of sodium hydroxide and dissolve them in deionized water to prepare a 5 mol / L precipitant.

[0027] (3) Add 1.5 g of sodium nitrate to the mixture after treatment in step (1), and mix them ultrasonically at 50° C. for 6 hours to obtain a mixed solution. Then, the mixed solution and the solution of step (2) are added dropwise to the same container using a peristaltic pump in a co-current addition strategy, and are added dropwise at 60° C. at a flow rate of 0.1 ml / min until the pH value reaches 7.5.

[0028] (4) The mixture treated in step (3) was subjected to rotary evaporation at 50° C. for 10 h, and then washed with deionized water and filtered to obtain a filter cake.

[0029] (5) The obtained filter cake was vacuum dried at 80°C for 12 h and finally dried under argon atmosphere at a space velocity of 4000 h -1 , calcined at 800℃ for 10h to obtain Na-CoFeO X catalyst.

[0030] The catalyst was first activated at 500 °C for 5 h under hydrogen conditions with a gas space velocity of 1000 h -1 Then, the volume ratio of H2 to CO was 5, the reaction temperature was 260℃, the reaction pressure was 5MPa, and the synthesis gas space velocity was 4000h -1 The reaction was carried out under the conditions of , and the results are shown in Table 1.

[0031] Example 3

[0032] (1) Take 2 g of cobalt hydrochloride and 0.5 g of ferric nitrate and dissolve them in 50 ml of ethanol and mix well.

[0033] (2) Take 5 g of ammonium carbonate and dissolve it in deionized water to prepare a 5 mol / L precipitant.

[0034] (3) Add 2.0 g of sodium nitrate to the mixture after treatment in step (1), and mix them ultrasonically at 50° C. for 6 hours to obtain a mixed solution. Then, the mixed solution and the solution of step (2) are added dropwise to the same container using a peristaltic pump in a co-current addition strategy, and then added dropwise at 80° C. at a flow rate of 0.5 ml / min until the pH value reaches 9.

[0035] (4) The mixture treated in step (3) was subjected to rotary evaporation at 50° C. for 10 h, and then washed with deionized water and filtered to obtain a filter cake.

[0036] (5) The obtained filter cake was vacuum dried at 80°C for 12 h and finally dried under argon atmosphere at a space velocity of 4000 h -1 , calcined at 900℃ for 10h to obtain Na-CoFeO X The catalyst was first activated under hydrogen conditions at 500 °C for 5 h, with a gas space velocity of 1000 h -1 Then, the volume ratio of H2 to CO was 2, the reaction temperature was 240℃, the reaction pressure was 5MPa, and the synthesis gas space velocity was 4000h -1 The reaction was carried out under the conditions of , and the results are shown in Table 1.

[0037] Example 4

[0038] (1) Take 3 g of cobalt sulfate and 0.8 g of ferric chloride, dissolve them in 50 ml of ethanol and mix well.

[0039] (2) Take 4.5 g of ammonium chloride and dissolve it in deionized water to prepare a 4 mol / L precipitant.

[0040] (3) Add 1.0 g of sodium carbonate to the mixture after treatment in step (1), and mix them ultrasonically at 50° C. for 6 hours to obtain a mixed solution. Then, the mixed solution and the solution of step (2) are added dropwise to the same container using a peristaltic pump in a co-current addition strategy, and are added dropwise at 80° C. at a flow rate of 0.3 ml / min until the pH reaches 8.

[0041] (4) The mixture treated in step (3) was subjected to rotary evaporation at 70° C. for 10 h, and then washed with deionized water and filtered to obtain a filter cake.

[0042] (5) The obtained filter cake was vacuum dried at 80°C for 12 h and finally dried under argon atmosphere at a space velocity of 3000 h -1 , calcined at 800℃ for 10h to obtain Na-CoFeO X The catalyst was first activated under hydrogen conditions at 500 °C for 5 h, with a gas space velocity of 500 h -1 Then, the volume ratio of H2 to CO was 5, the reaction temperature was 280℃, the reaction pressure was 6MPa, and the synthesis gas space velocity was 4000h -1 The reaction was carried out under the conditions of , and the results are shown in Table 1.

[0043] Example 5

[0044] (1) Take 5 g of cobalt acetate and 1.5 g of ferric chloride and dissolve them in 80 ml of ethanol and mix well.

[0045] (2) Take 3.5 g of potassium hydroxide and 4 g of ammonium chloride and dissolve them in deionized water to prepare an 8 mol / L precipitant.

[0046] (3) Add 1.5 g of sodium chloride to the mixture after treatment in step (1), and mix them ultrasonically at 50° C. for 6 hours to obtain a mixed solution. Then, the mixed solution and the solution of step (2) are added dropwise to the same container using a peristaltic pump in a co-current addition strategy, and are added dropwise at 80° C. at a flow rate of 0.2 ml / min until the pH value reaches 7.

[0047] (4) The mixture treated in step (3) was subjected to rotary evaporation at 70° C. for 15 h, and then washed with deionized water and filtered to obtain a filter cake.

[0048] (5) The obtained filter cake was vacuum dried at 80°C for 12 h and finally dried under argon atmosphere at a space velocity of 4000 h -1 , calcined at 1000℃ for 10h to obtain Na-CoFeO X The catalyst was first activated under hydrogen conditions at 600 °C for 5 h, with a gas space velocity of 500 h -1Then, the volume ratio of H2 to CO was 1, the reaction temperature was 280℃, the reaction pressure was 6MPa, and the synthesis gas space velocity was 4000h -1 The reaction was carried out under the conditions of , and the results are shown in Table 1.

[0049] Example 6

[0050] (1) Take 4 g of cobalt acetate and 0.5 g of ferric acetate, dissolve them in 50 ml of ethanol and mix well.

[0051] (2) Take 6 g of sodium hydroxide and dissolve it in deionized water to prepare a 5 mol / L precipitant.

[0052] (3) Add 2.0 g of sodium nitrate to the mixture after treatment in step (1), and mix them ultrasonically at 50° C. for 6 hours to obtain a mixed solution. Then, the mixed solution and the solution in step (2) are added dropwise to the same container using a peristaltic pump in a co-current addition strategy, and are added dropwise at 100° C. at a flow rate of 0.2 ml / min until the pH value reaches 9.

[0053] (4) The mixture treated in step (3) was subjected to rotary evaporation at 80° C. for 8 h, and then washed with deionized water and filtered to obtain a filter cake.

[0054] (5) The obtained filter cake was vacuum dried at 70°C for 12 h and finally dried under an argon atmosphere at a space velocity of 3000 h -1 , calcined at 800℃ for 10h to obtain Na-CoFeO X The catalyst was first activated under hydrogen conditions at 500 °C for 5 h, with a gas space velocity of 800 h -1 Then, the volume ratio of H2 to CO was 3, the reaction temperature was 280℃, the reaction pressure was 6MPa, and the synthesis gas space velocity was 4000h -1 The reaction was carried out under the conditions of , and the results are shown in Table 1.

[0055] Comparative Example 1

[0056] (1) Take 4 g of cobalt acetate and 0.5 g of ferric acetate and dissolve them in 50 ml of deionized water.

[0057] (2) After ultrasonic treatment of the obtained mixture for 5 h, 2 g of sodium nitrate was added and stirred until the mixture was uniform.

[0058] (3) adding 5 mol / L urea aqueous solution to carry out precipitation reaction, and filtering and washing to obtain a filter cake;

[0059] (4) The obtained filter cake was dried in air at 70°C for 12 h and finally dried in a nitrogen atmosphere at a space velocity of 3000 h -1 The Na-CoFe catalyst was first activated at 500°C for 5 h under hydrogen conditions with a gas space velocity of 1000 h -1Then, the volume ratio of H2 to CO was 3, the reaction temperature was 280℃, the reaction pressure was 6MPa, and the synthesis gas space velocity was 4000h -1 The reaction was carried out under the conditions of

[0060] Comparative Example 2

[0061] (1) Take 5 g of cobalt acetate and 1.5 g of sodium chloride and dissolve them in 10 ml of deionized water;

[0062] (2) adding 8 g of ferroferric oxide carrier for impregnation;

[0063] (3) The obtained solid was dried in air at 80°C for 12 h and finally dried in a nitrogen atmosphere at a space velocity of 4000 h -1 , and calcined at 1000℃ for 10h to obtain Na-Co / Fe3O4 catalyst.

[0064] The catalyst was first activated at 600 °C for 5 h under hydrogen conditions with a gas space velocity of 2000 h -1 Then, the volume ratio of H2 to CO was 5, the reaction temperature was 280℃, the reaction pressure was 6MPa, and the synthesis gas space velocity was 4000h -1 The reaction was carried out under the conditions of , and the results are shown in Table 1.

[0065] Table 1 Catalyst CO hydrogenation reaction performance evaluation and product analysis.

[0066]

[0067] As can be seen from Table 1, compared with the conventional catalyst preparation methods of Comparative Examples 1 and 2, the parallel flow titration solid solution catalyst preparation method used in the present invention successfully prepared Na-CoFeO X The catalyst improves the adsorption and carbon chain insertion capabilities of CO through oxygen vacancies in the catalyst, thereby improving the CO conversion rate and the selectivity of high-carbon alcohols and olefins. The metal cobalt and iron are carbonized into carbides during the reaction process to inhibit the hydrogenation reaction and reduce the generation of CH4. At the same time, the strong interaction between the two metals is used to make the reaction active center easy to control and stabilize, thereby improving the stability of the catalyst.

[0068] The above describes the specific embodiments of the present invention. It should be noted that the present invention is not limited to the above specific embodiments, and any modifications, equivalent replacements, improvements, etc. made within the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a Na-modified cobalt-iron solid solution catalyst, characterized in that: The preparation process includes: (1) dissolving a soluble salt of Co and a soluble salt of Fe in 20-100 ml of ethanol at a metal molar ratio of 5:1-50:1 (preferably 10:1-40:1, more preferably 20:1-30:1) to prepare a mixture; wherein the mass concentration of Co is 0.5 mg / ml-100 mg / ml (preferably 10 mg / ml-90 mg / ml, more preferably 20 mg / ml-50 mg / ml); (2) preparing a 0.1 mol / L to 10 mol / L aqueous solution of a precipitant; (3) adding 0.5-3 g (preferably 1-3 g, more preferably 2-3 g) of a soluble salt of Na to 50 g of the mixture treated in step (1), and ultrasonically mixing the mixture at 35-50° C. (preferably 40-50° C., more preferably 45-50° C.) for 6-10 hours (preferably 8-10 hours, more preferably 9-10 hours) to obtain a mixed solution, and then dripping the mixed solution and the solution of step (2) into the same container by a co-current dripping strategy, and dripping the mixture at 50-150° C. (preferably 70-120° C., more preferably 80-100° C.) at a flow rate of 0.01 ml / min-0.5 ml / min (preferably 0.1 ml / min-0.5 ml / min, more preferably 0.1 ml / min-0.3 ml / min) until the pH value is 7-10 to obtain a precipitation mixture; (4) treating the mixture after the treatment in step (3) at 50-100° C. (preferably 70-90° C., more preferably 80-90° C.) for 5-15 h (preferably 7-15 h, more preferably 9-12 h), then washing with water and filtering to obtain a filter cake; (5) drying the filter cake obtained in step (4), and then calcining it at 600-1100° C. (preferably 700-1000° C., more preferably 800-1000° C.) for 5-15 h (preferably 6-12 h, more preferably 8-12 h) under an inert atmosphere to obtain Na-CoFeO X Solid solution catalyst.

2. The preparation method according to claim 1, characterized in that: The soluble salt of Co is one or more of cobalt nitrate, cobalt acetate, cobalt sulfate and cobalt hydrochloride; the soluble salt of Fe is one or more of ferric nitrate, ferric acetate, ferric chloride and ferrous sulfate.

3. The preparation method according to claim 1, characterized in that: The soluble salt of Na is one or more of sodium nitrate, sodium chloride, sodium carbonate and sodium sulfate; and the inert atmosphere is one or more of helium, nitrogen and argon.

4. The preparation method according to claim 1, characterized in that: The precipitant is one or more of potassium hydroxide, ammonium chloride, ammonium carbonate and sodium hydroxide; Step (5) The filter cake obtained in step (4) is dried under vacuum at 50-100°C for 5-20h, and then dried at a gas space velocity of 2000-4000h -1 (Preferably 2500-3500h -1 , more preferably 2800-3300h -1 ) in an argon atmosphere at 600-1100°C for 5-15h to obtain Na-CoFeO X Solid solution catalyst.

5. A catalyst prepared by the preparation method according to any one of claims 1 to 4.

6. The catalyst according to claim 5, characterized in that: The catalyst consists of a solid solution component and an auxiliary component, wherein the solid solution component is a cobalt-iron solid solution, the auxiliary component is a simple substance or oxide of sodium, and the reaction active center is a cobalt-iron solid solution, cobalt and cobalt carbide or cobalt oxide species and a simple substance or oxide of sodium.

7. Use of the catalyst according to claim 5 or 6 in catalyzing the conversion reaction of synthesis gas to produce higher alcohols and co-produce higher olefins.

8. The use according to claim 7, characterized in that The catalyst precursor is reduced and activated before use. The reducing gas is usually hydrogen or a mixture of hydrogen and nitrogen (the volume ratio of hydrogen to nitrogen is 1% to 99% (preferably 10% to 80%, more preferably 20% to 70%), the reduction activation temperature is 300 to 600°C (preferably 350 to 500°C, more preferably 400 to 500°C), the reduction activation time is 1 to 50h (preferably 5 to 40h, more preferably 20 to 40h), and the gas space velocity is 200-10000h -1 (Preferably 1000~8000h -1 , more preferably 2000~6000h -1 ).

9. The use according to claim 7 or 8, characterized in that: The volume ratio of H2 to CO in the synthesis gas is 0.5-10 (preferably 1-8, more preferably 2-5), the reaction temperature is 180-350°C (preferably 200-350°C, more preferably 200-300°C), the reaction pressure is 0.5-10MPa (preferably 1-8MPa, more preferably 2-5MPa), and the synthesis gas space velocity is 500-8000h -1 (Preferably 2000~8000h -1 , more preferably 2000~6000h -1 ).

10. The use according to claim 7 or 8, characterized in that Higher carbon alcohols refer to alcohols with six or more carbon atoms, and higher carbon olefins refer to α-olefins with five or more carbon atoms.

Citation Information

Patent Citations

  • Cu-Fe-based catalyst used in synthesis of higher alcohol with synthetic gas, preparation method thereof and application thereof to process for synthesizing higher alcohol with synthetic gas

    CN102319575A

  • Copper-based nano catalyst for preparing high-carbon alcohol from synthetic gas as well as preparation method and application thereof

    CN102500374B

  • A mixed oxide catalyst for the preparation of higher alcohols from syngas

    CN105664964B

  • Fischer-Tropsch synthesis catalyst and preparation method and application thereof

    CN101869840A

  • Catalyst for directly converting synthesis gas into long-chain alkene by one-step method

    CN105498798A